2020
DOI: 10.22541/au.160239783.34402594/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Psychological Impact of the COVID-19 Pandemic on Egyptian Diabetic Patients

Abstract: Background: Since the onset of the COVID-19 pandemic, concerns about health-related and economic hazards of the virus, the restrictions imposed by the public health measures, the lack of social interactions, and the financial losses have affected people's mental health in various ways. People with diabetes are more vulnerable to comorbid mental illness that may interfere with treatment adherence and disease prognosis. This study explores the psychological state of Egyptian patients suffering from diabetes mell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…A total of 226 subjects participated in the survey, out of which 118 (52.2%) were females and 108 (47.8%) were males, which is in accordance with the study carried out by Shaltout et al where a female preponderance was observed [12]. In our study, the participants were divided into 3 age groups.…”
Section: Discussionsupporting
confidence: 87%
“…A total of 226 subjects participated in the survey, out of which 118 (52.2%) were females and 108 (47.8%) were males, which is in accordance with the study carried out by Shaltout et al where a female preponderance was observed [12]. In our study, the participants were divided into 3 age groups.…”
Section: Discussionsupporting
confidence: 87%